KRITIK SOSIAL DAN NILAI MORAL DALAM CERPEN “PERIHAL ORANG MISKIN YANG BAHAGIA” KARYA AGUS NOOR - Ihsan Aldi Putra (IKIP Siliwangi, 2020)
Social criticism contained in literary works indicates irregularities in social life. Literature that is present in the midst of society can be used as a social controller. One of the literary works capable of this function is a short story. In every literary work including short stories, like other arts, made not only for entertainment. Furthermore, every work of art tries to convey a message about the values that the creator considers correct. In order to understand social criticism and values, the reader must first analyze it in order to grasp the meaning conveyed by the author. Therefore, through this article researchers are interested in discussing the things described above. This article analyzes the social criticism and moral values contained in the short story